Dynamics of Women Entrepreneurs in Sultanate of Oman – Opportunities and Obstacles - Chavali, Kavita (International Review of Management and Marketing, 2016)
The study is a questionnaire based purposive sampling of 100 respondents in Oman. The Arab world is a patriarchal society with unwritten rules and the objective of the study is to uncover the opportunities available to Omani women and the obstacles which they face as an entrepreneur as well as in the process of becoming an entrepreneur. The study also looks into the basic differences in the perception of women who are entrepreneurs and women who would like to become entrepreneurs in the future. ANOVA is used for hypothesis testing. Factor Analysis is used to explore the motivational factors, obstacles faced and success factors of women entrepreneurs and future entrepreneurs in Oman. Keywords: Entrepreneurship, Motivation, Obstacles, Success factors, Sultanate of Oman. JEL Classifications: L26